Pengaruh Peran Guru Terhadap Optimalisasi Tumbuh dan Kembang (Sosial) pada Anak Di TPA Ar-Rahmah Pondok Pesantren Nurul Jadid Paiton Probolinggo - Munir, Zainal (Jurnal Keperawatan Profesional, 2022)
The process of growth and development is the main process in the process of a child's life. The process of growth and development that lasts 1000 days of birth is the responsibility of all of us, both biological parents and non-biological parents. Early education in children has become a government concern. The assumption that education can only start after elementary school age is not true, even education that starts at kindergarten age is actually too late. This research is an intervention research by providing intervention to children by TPA Ar-Rahman teacher with 1 pre-post test group with developmental stimulus method in the social sector. The technique used is total sampling, namely all Ar-Rahman TPA teachers. The data was collected by using a paired T-test approach through a pre-post test. The benefits of future research are expected to add insight to teachers about concepts, stimulation and screening of preschool children's growth and development and teachers can make early detection of growth and development in preschool children appropriately. This good result is expected to be followed by the implementation of early detection of growth and development in preschool children independently by the school, then reported to the health service center. so that the scope of the early detection program for child growth and development increases. The determining factor for the development of children both physically and mentally is the role of parents, especially the role of a mother, because mothers are the first and foremost educators for children who are born until they grow up. In the process of forming knowledge, through various parenting styles conveyed by a mother as the first educator, it is very important. Education in the family plays a very important role in developing character, personality, cultural values, religious and moral values, and simple skills